PENGARUH DISIPLIN KERJA, KOMITMEN ORGANISASI DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI PADA KEMENTRIAN AGAMA KABUPATEN SERANG - Ipan Hilmawan, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of work discipline, organizational commitment and teamwork on employee performance at the Ministry of Religion in Serang Regency. The population in this study were employees at the Ministry of Religion in Serang Regency, totaling 123 people. The sample of this study was 95 respondents who were determined by the Slovin formula and withdrawal of the sample using random sampling. The data analysis method uses the help of IBM SPSS 23 software. The results of this study indicate that: 1) Work discipline has a positive and significant effect on employee performance, 2) Organizational commitment has a positive and significant effect on employee performance, and 3) Team collaboration has no positive and no significant effect on employee performance.